Spatial ecology, landscapes, and the geography of vector-borne disease: A multi-disciplinary review. (September 2015) - Jamison, Amanda; Tuttle, Elaina; Jensen, Ryan; Bierly, Greg; Gonser, Rusty
Abstract: According to the World Health Organization, more than half the world's population is at risk for vector-borne illnesses such as malaria and Lyme disease. Climate change and other anthropogenic factors have further increased the incidence of vector-borne diseases in several parts of the world. To prevent the spread of these devastating diseases, scientists have focused their efforts on controlling the ever-expanding distributions of arthropod vectors. Since arthropod vectors are dependent on environmental factors, geospatial technologies, such as geographic information systems and remote sensing, may assist in their control and eradication by allowing researchers to collect, manage and analyze environmental data with greater precision and accuracy than ever before. Many studies of vector-borne disease have begun to integrate geospatial technologies, such as remote sensing-derived vegetation indices, with traditional ecological data. Here we review the use of multidisciplinary research incorporating climate, geospatial technologies, and ecology in the study and control of disease vectors. Suggestions for future research combining these disciplines are discussed. Highlights: We review the how GIS can provide insights to vector-borne disease. We review the main vectors of disease inflicting humans. We examine potential areas for research collaborations. Technology has advanced that we have better resolution to predict outbreaks. Multidisciplinary research should be the norm in epidemiology.